Case report: Mononeuropathy multiplex of extranodal natural killer/T-cell lymphoma misdiagnosed as systemic vasculitis - Shi, Jiayu; Niu, Jingwen; Wu, Di; Zhang, Lei; Huang, Yangyu; Zhang, Hui; Guan, Hongzhi; Liu, Mingsheng; Guan, Yuzhou (Frontiers in Neurology, 2023)
Background: Extranodal NK/T-cell lymphoma (ENKTL) is an aggressive non-Hodgkin lymphoma that typically develops in the upper aerodigestive tract. Case presentation: We encountered an ENKTL patient presented with purpura-like rashes and foot drop as initial symptoms, who later developed other peripheral nerves involvement. Nerve conduction study of both motor nerve and sensory nerve showed axonal damage resembling mononeuropathy multiplex. Although the initial response to steroids was encouraging, the patient's symptoms reappeared and aggravated. Biopsy of abdominal subcutaneous fat tissue with additional immunohistochemistry revealed neoplastic NK/T lymphocytes. Conclusions: We reported the first case presented as mononeuropathy multiplex as initial clinical manifestation in ENKTL patients. Lymphoma should be considered in diagnosis of atypical mononeuropathy multiplex patients.